2021
DOI: 10.21203/rs.3.rs-173586/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

FASN Inhibition as a Potential Treatment for Endocrine-Resistant Breast Cancer

Abstract: PurposeThe majority of breast cancers are estrogen receptor (ERα) positive making endocrine therapy a mainstay for these patients. Unfortunately, resistance to endocrine therapy is a common occurrence. Fatty acid synthase (FASN) is a key enzyme in lipid biosynthesis and its expression is commensurate with tumor grade and resistance to numerous therapies. MethodsThe effect of the FASN inhibitor TVB-3166 on ERα expression and cell growth was characterized in tamoxifen resistant cell lines, xenografts, and patien… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…We tested the antitumor effects of TVB3166, a selective commercial FASN inhibitor [40], in OE19, N87, OE33 and GTR0455 gastrospheres.. TVB3166, tested at different concentrations, impaired in a dose-dependent manner the GFE (%) of GCSCs derived from the T-sensitive and T-resistant cell lines compared with vehicle (DMSO)-treated gastrospheres, with a statistical significance ranging from P < 0.05 to P < 0.005 (Fig. 4a).…”
Section: Inhibition Of Fasn Expression/activity Targets Gcscs In Her2...mentioning
confidence: 99%
“…We tested the antitumor effects of TVB3166, a selective commercial FASN inhibitor [40], in OE19, N87, OE33 and GTR0455 gastrospheres.. TVB3166, tested at different concentrations, impaired in a dose-dependent manner the GFE (%) of GCSCs derived from the T-sensitive and T-resistant cell lines compared with vehicle (DMSO)-treated gastrospheres, with a statistical significance ranging from P < 0.05 to P < 0.005 (Fig. 4a).…”
Section: Inhibition Of Fasn Expression/activity Targets Gcscs In Her2...mentioning
confidence: 99%
“…Indeed, “in vitro” and “in vivo” treatment with a FASN inhibitor restored the sensitivity to the anti‐tumor activity of tamoxifen and fulvestrant 200 . Inhibition of FASN activity was also associated with a marked reduction of growth in tamoxifen‐resistant cell lines and tumor xenografts 202 …”
Section: Obesity and Endocrine Response In Breast Cancer: Proposed Me...mentioning
confidence: 99%
“…Two selective and potent FASN inhibitors, TVB‐3166 and TVB‐3664, were discovered and used in ovarian, lung, prostate and pancreatic cancer mouse models, which presented that inhibiting FASN in combination with taxane therapy inhibited tumor cell growth both in vitro and in vivo , possibly by disrupting tubulin palmitoylation, expression and microtubule organization [140]. Mechanistically, it is negotiable how exactly TVB‐3166 exerts its antitumor effect as another study showed that TVB‐3166 treatment alters ERα subcellular localization and reduces ERα levels by inducing endoplasmic reticulum stress, and exhibits antitumor activity in tamoxifen‐resistant breast tumor cells [141] (Table 1). Further investigations are warranted on this issue.…”
Section: Targeting Protein Palmitoylation In Cancermentioning
confidence: 99%